2021
DOI: 10.21037/jtd-21-106
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of etoposide capsules as maintenance therapy for patients with extensive-stage small cell lung cancer: a prospective two-stage, two-center study

Abstract: Background: Due to the high incidence and mortality of lung cancer, and etoposide is the standard firstline chemotherapy for small cell lung cancer, to evaluate the efficacy and safety of etoposide capsules at different doses as maintenance therapy for patients with extensive-stage small cell lung cancer (ES-SCLC) who show a response to etoposide plus platinum. Methods: The study was divided into two stages: stage I, a single-center, one-arm prospective study, and stage II, a multicenter, controlled non-random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The research on maintenance treatment of SCLC has been involved in the fields of chemotherapy, molecular targeted drugs, and immunotherapy. The prospective study (NCT02179528) stated that etoposide capsules as maintenance therapy significantly prolonged the survival time in ES-SCLC patients (PFS: 7.87 vs. 5.90 months; OS: 15.03 vs. 14.33 months) [18]. The HOT1401/NJLCG1401 trial indicated that maintenance therapy with cisplatin plus irinotecan or amrubicin might be effective in some ES-SCLC patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…The research on maintenance treatment of SCLC has been involved in the fields of chemotherapy, molecular targeted drugs, and immunotherapy. The prospective study (NCT02179528) stated that etoposide capsules as maintenance therapy significantly prolonged the survival time in ES-SCLC patients (PFS: 7.87 vs. 5.90 months; OS: 15.03 vs. 14.33 months) [18]. The HOT1401/NJLCG1401 trial indicated that maintenance therapy with cisplatin plus irinotecan or amrubicin might be effective in some ES-SCLC patients [19].…”
Section: Discussionmentioning
confidence: 99%